Customer-perceived importance of restaurant attributes for casual dining, fast food and coffee shops - Wiastuti, Rachel Dyah; Rashid, Basri (Turyzm/Tourism, 2024)
The study aims to explore the restaurant attributes that fit specifically into three different types of food and beverage businesses: casual dining, fast food and coffee shops. The notion is based on customer-perceived importance proposed for a specific one-generation cohort. There were 519 respondents from Generation Z, gathered in mid-2023 using both printed and online questionnaires. Data were analyzed using factor analysis with SPSS. The restaurant attribute consisted of five types based on past literature, food, service, ambiance, experience and safety. However, the findings for the Gen Z context, resolved into only three types: casual dining, fast food and coffee shops, consisting of 30, 23 and 27 items respectively. To add, despite female Gen Z demanding more cleanliness than its male counterpart, both agree that quality of taste is the most important attribute for choosing a restaurant. The result of this study provides valuable information for restaurant businesses to better grasp Gen Z market’s dining habits. Restaurant operators will understand how customers evaluate the relevance of restaurant qualities differently.